2009
DOI: 10.1111/j.1651-2227.2008.01207.x
|View full text |Cite
|
Sign up to set email alerts
|

Agrichemicals in surface water and birth defects in the United States

Abstract: Objectives: To investigate if live births conceived in months when surface water agrichemicals are highest are at greater risk for birth defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(122 citation statements)
references
References 29 publications
4
110
2
4
Order By: Relevance
“…In addition, there was a stronger effect noted for infants conceived in spring, when pesticides were typically applied. A study also conducted in the USA reported higher rates of several birth defects, including spina bifida and CVS malformations, in infants conceived in the months with highest surface water concentrations of pesticides such as atrazine [4]. Regarding individual-level epidemiological studies, a casecontrol study in California found that women occupationally exposed to pesticides during pregnancy presented an increased risk of having a baby with a neural tube defect, among other anomalies [36].…”
Section: Ijomeh 2014;27(3) 482mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there was a stronger effect noted for infants conceived in spring, when pesticides were typically applied. A study also conducted in the USA reported higher rates of several birth defects, including spina bifida and CVS malformations, in infants conceived in the months with highest surface water concentrations of pesticides such as atrazine [4]. Regarding individual-level epidemiological studies, a casecontrol study in California found that women occupationally exposed to pesticides during pregnancy presented an increased risk of having a baby with a neural tube defect, among other anomalies [36].…”
Section: Ijomeh 2014;27(3) 482mentioning
confidence: 99%
“…In the USA, birth defects are the main cause of infant mortality, being responsible for 20.1% of the total number of deaths [4]. In Latin America, congenital anomalies are responsible for 25% of pediatric hospital admissions and they represent the 3rd cause of mortality among infants in the 1st year of life [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore agricultural areas should not be undervalued by existing assessments (Tillitt et al, 2010;Wu et al, 2010). Atrazine disrupts hormones was substantiated by epidemiological studies which found links between atrazine exposure and © 2017 Life Science Informatics Publication All rights reserved Peer review under responsibility of Life Science Informatics Publications 2017 July -August RJLBPCS 3(2) Page No.199 reproductive effects including low birth weight, increased risk of miscarriage, increased the frequency of congenital disability, and reduced male fertility (Swan et al, 2003;Winchester et al, 2009). At low concentrations as 0.1 to 1.0 µg L −1 incidences of hermaphroditic effects and feminization of Xenopus laevis (male African clawed frogs) have been reported (Hayes et al, 2002;Ralston-Hooper et al, 2009).…”
Section: Reproductive Effects and Endocrine Disruptionmentioning
confidence: 98%
“…In recent years, the frequent detection of ATZ and its degradation products in water supplies and concerns about ATZ potential endocrine/reproductive and neurological effects in wildlife and humans triggered several environmental and epidemiologic studies for assessment of possible human health hazards of ATZ and other triazine pesticides [1][2][3].…”
Section: Introductionmentioning
confidence: 99%